Indonesian Sea Sand Exports: UNCLOS Compliance v. Environmental Sustainability Dilemma Explored - Yordan Gunawan; Muhammad Praditya Dananjaya; Setiyantoro Wahyu Aditama; Muhammad Daffa Auliarizky Onielda (Jurnal Hukum, 2025)
This study aims to analyze the impact of Indonesia's sea sand exports on UNCLOS compliance and environmental sustainability. The methodology involved analyzing UNCLOS policies related to marine sediment exports and the environment, evaluating literature sources that included case studies and analyzing the impacts of sea sand exports, and fieldwork by conducting interviews with government officials, environmental experts, and local residents. The results highlight that Indonesia's export of marine sand violates UNCLOS and harms the environment. Therefore, sustainable measures are needed, including strict monitoring of exports, better environmental management, and involving communities in the decision-making process. In order to resolve this conflict, the Indonesian government needs to adopt a sustainable approach, recognize the impact on the environment, and involve various parties in an effort to maintain the sustainability of sea sand exports while complying with UNCLOS.